Penerapan keterampilan abad 21 di Kelas V sekolah dasar - Sukmanasa, Elly; Anwar, Wawan Syahiril; Novita, Lina (Universitas Sebelas Maret, 2023)
The 2013 curriculum was designed and developed to facilitate skilled teachers and students in increasing learning interactions, especially in the 21st century. 21st century skills are a challenge for teachers and students to be able to adapt to the current era. 21st century skills need to be integrated and implemented in learning with the aim of creating generations according to current needs and demands. This study aims to implement 21st century skills by developing learning tools with TPACK, HOTS, and STEAM or STEM content, with problem- and project-based learning models (PBL and PJBL). The method used is descriptive analysis through the stages of observation, interviews to identify problems, conducting group discussion forums, making instrument angles, observation guidelines, and interview guidelines. Data collection was carried out on V grade elementary school students, totaling 30 people by using an interview guide questionnaire and a checklist for observation. The research findings are evidenced by three stages, namely learning planning through learning tools that include 21st century or 4C skills, implementing the learning process and evaluating the implementation of learning. The data shows that students are able to participate in activities oriented to the 4C skills, Critical Thinking and Problem Solving, Creativity and Innovative, Collaborative, and Communicative. Through 21st century or 4C skills, students are more active and able to collaborate with other students, and have self-confidence.